1997
DOI: 10.1002/(sici)1099-0755(199709)7:3<199::aid-aqc228>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the habitat available for 0+Rutilus rutilus (L.) in a regulated river

Abstract: 1. Habitat availability for 0+ Rutilus rutilus (L.) was determined at four sites in the regulated River Great Ouse, Eastern England, using a modified version of the Instream Flow Incremental Methodology. Discharge–habitat relationships were then calculated using a modified version of the Physical Habitat Simulation (PHABSIM) computer package. A weighted usable area (WUA) time series was generated using the discharge–habitat models.  2. Habitat availability varied between sites and with discharge, although at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Thus, Heggenes and Saltveit (1990) attributed variation in habitat use of Atlantic salmon (Salmo salar) and brown trout (S. trutta) to different habitat availabilities and to varying discharge and temperature, respectively, and several authors have since reported between-site (e.g. Bozek and Rahel, 1992;Garner, 1997b) as well as diel differences in suitability curves (Harris et al, 1992;Roussel et al, 1999). Finally, the shortcomings of pooling may be exacerbated whenever changes in stream flows contribute to HSC variation (Shirvell, 1990;Heggenes et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Heggenes and Saltveit (1990) attributed variation in habitat use of Atlantic salmon (Salmo salar) and brown trout (S. trutta) to different habitat availabilities and to varying discharge and temperature, respectively, and several authors have since reported between-site (e.g. Bozek and Rahel, 1992;Garner, 1997b) as well as diel differences in suitability curves (Harris et al, 1992;Roussel et al, 1999). Finally, the shortcomings of pooling may be exacerbated whenever changes in stream flows contribute to HSC variation (Shirvell, 1990;Heggenes et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the habitat suitability curves with those based on expert opinion (Armitage and Ladle, 1991) revealed large differences, both in the shape of the curves and in the position of the optima. In general, Armitage and Ladle (1991) underestimated depth preferences and overestimated velocity suitability by comparison with the model of Garner and Mann (1996). At winter temperatures of 5±8 C, Garner and Mann (1996) estimated that optimum velocity would be`5 cm s À1 .…”
Section: Spawning Habitats For Cyprinidaementioning
confidence: 99%
“…In general, Armitage and Ladle (1991) underestimated depth preferences and overestimated velocity suitability by comparison with the model of Garner and Mann (1996). At winter temperatures of 5±8 C, Garner and Mann (1996) estimated that optimum velocity would be`5 cm s À1 . Under moderate to high discharge conditions the extent of suitable habitat in the main channels and some side channels becomes considerably reduced (Pinder et al, 1991).…”
Section: Spawning Habitats For Cyprinidaementioning
confidence: 99%
See 2 more Smart Citations